Distribution in plant, substrate and leachate of paclobutrazol following application to containerized Nerium oleander L. seedlings - Ochoa, J.; Franco, J.A.; Bañón, S.; Fernández, J.A.; Fernández, J.A. (Spanish Journal of Agricultural Research, 2009)
Paclobutrazol (PBZ) is a retardant often used in potted ornamental plants to control their growth and compactness. The distribution in plant, substrate and leachate of PBZ applied to containerized oleander seedlings were studied after a single liquid drench application to the substrate surface (20 mg a.i. per plant) in a nursery dedicated to pot production in SE Spain. PBZ significantly reduced all growth parameters, providing more compact plants of good commercial value and confirming its ability to reduce the vertical growth of native oleander in the nursery. The level of PBZ residues in leaves was higher at the end of pot cultivation (156 days post PBZ application) than at the first sampling time (30 days after PBZ application), whereas the level in stems decreased for the same period of time. PBZ residues in roots remained constant during the experimental period. The high level of PBZ residues detected in the substrate 30 days after application had decreased significantly (by 67%) by the end of the experiment. A greater leaching fraction was detected for PBZ-treated seedlings and so a greater amount of PBZ was leached into the nursery soil with the irrigation water at the end of the experiment. This greater amount of PBZ leached into the soil represents an important way of contamination in the nursery and a substantial risk to the environment.